2018
DOI: 10.3389/fimmu.2018.01181
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Syndrome Nephropathy: From Pathogenesis to Treatment

Abstract: Kidney damage is a well-recognized complication of the antiphospholipid syndrome (APS), either primary or systemic lupus erythematosus (SLE)-associated APS. Kidney involvement in APS involves a variety of manifestations, such as renal artery thrombosis or stenosis, renal vein thrombosis, allograft loss due to thrombosis after kidney transplantation, and injury to the renal microvasculature, also known as APS nephropathy. Biopsy in patients with APS nephropathy includes acute thrombotic microangiopathy lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 62 publications
0
32
0
5
Order By: Relevance
“…This results in post-thrombotic lesions in arterioles and glomeruli, as well as focal cortical atrophy with interstitial fibrosis on renal biopsy. The severity of APS nephropathy can range from mild chronic renal impairment with variable degrees of proteinuria and haematuria to acute renal failure with associated multiorgan involvement 13 14. Hypertension is highly prevalent in APS nephropathy and has been described as the hallmark feature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This results in post-thrombotic lesions in arterioles and glomeruli, as well as focal cortical atrophy with interstitial fibrosis on renal biopsy. The severity of APS nephropathy can range from mild chronic renal impairment with variable degrees of proteinuria and haematuria to acute renal failure with associated multiorgan involvement 13 14. Hypertension is highly prevalent in APS nephropathy and has been described as the hallmark feature of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidneys, aPL‐associated nephropathy (APLN) comprises acute conditions such as thrombotic microangiopathy (TMA) and more chronic lesions with vascular damage that are often difficult to delineate from kidney damage caused by hypertension. APLN was recently reviewed , and notably, this condition is similar in SLE and pAPS, but cannot from the clinical presentation be distinguished from lupus nephritis, unless a biopsy is performed. Tektonidou et al demonstrated that these lesions are common in SLE patients with aPL and that they are associated with hypertension and impaired renal function .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Electron microscopy (original magnification × 4,800) revealed a glomerulus with mesangial matrix collapse and resultant capillary loop collapse ( CL b in D ), along with subendothelial electron‐lucent widening ( dashed arrow in D )—classic ultrastructural features of acute TMA and mesangiolysis (urinary space [ US ], mesangial cell nucleus [ MCN ], podocyte [ P ], and a normal capillary loop [ CL a ] are also seen in D ). Antiphospholipid antibody–associated nephropathy as pure TMA without concurrent lupus nephritis is rarely described in the literature . Further evaluation revealed mitral valvulitis with mitral regurgitation; right atrial thrombus; and thrombi in jugular, basilic, and brachial veins.…”
mentioning
confidence: 95%
“…. Antiphospholipid antibody-associated nephropathy as pure TMA without concurrent lupus nephritis is rarely described in the literature (2,3). Further evaluation revealed mitral valvulitis with mitral regurgitation; right atrial thrombus; and thrombi in jugular, basilic, and brachial veins.…”
mentioning
confidence: 99%